Awareness of population regarding the effects of diabetes on dental implant treatment in Jeddah, Saudi Arabia - Almehmadi, Ahmad H. (Heliyon, 2019)
OBJECTIVE: Diabetes mellitus (DM) has several complications. Delayed wound healing, microvascular disease and an impaired response to infections are complications that can have a direct bearing on dental implant therapy. This paper studies the awareness of the population with regard to the effect of DM on dental implant treatment. MATERIALS AND METHODS: A validated, close-ended questionnaire was distributed to 506 randomly selected mall-goers in the city of Jeddah. Responses were coded and entered into spreadsheet software (SPSS, IBM). The frequency distribution of the responses was calculated, and inferences were drawn. RESULTS: The study revealed that the majority of the sample were females (62.8%), did not have diabetes (80.4%) and reported a positive family history of diabetes (87.4%). Most of the respondents (56%) believed that uncontrolled diabetes can lead to implant loss and that diabetes affects the healing process (91.6%). Many patients (42%) responded that diabetes could be treated with dental implants if the blood sugar level was controlled. CONCLUSION: The studied sample revealed a satisfactory level of awareness regarding the association of diabetes and oral hygiene in dental implant therapy. However, there is less than adequate knowledge about the effects of diabetes on dental implants, as the majority of the respondents believe that only controlled diabetics can avail dental implant treatment.